Comparing the SDG-classification systems of Dimensions, InCites and SciVal for the University of Helsinki - Petri Turunen; Terhi Sandgren (Information Research: An International Electronic Journal)
Introduction. We determined how the publications of the University of Helsinki were attributed to the United Nations sustainable development goals (SDGs) in three different databases. The databases were Dimensions, Scopus and Web of Science. We also looked at the overlaps.